Kontribusi Green Accounting dalam Mendukung Pencapaian Sustainable Development Goals (SDGs) pada Perusahaan Sektor Energi - Syntha Noviyana; Komsi Koranti; Sriyanto; Rengganis Dwianti Putri (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to determine the effect of Green Accounting on Sustainable Development Goals (Sdgs) in Energy Sector Companies Listed on Bei for the 2018- 2023 Period.The sample used in this study were energy sector companies that were included in the main board on the Indonesia Stock Exchange, registered as PROPER participants and who had complete data for research. The sampling technique used is purposive sampling, namely by selecting samples based on criteria determined by the author, obtained as many as 8 companies during the 2018-2023 period. The analysis methods used in this study are Descriptive Statistical Test, Assessing the Overall Model, Coefficient of Determination, Testing the Feasibility of the Logistic Regression Model, Classification Mean, Wald Test and Omnibus Test of Model Coefficients.The results of this study indicate that Green Accounting variables which are proxied by Environmental Costs, Environmental Performance and Environmental Activities have a significant influence on Sustainable Development Goals (SDGs). Meanwhile, the Environmentally Friendly Product variable does not have a significant influence on Sustainable Development Goals (SDGs).